ANALYSIS FORECASTING OF OPERATIONAL EXPENSE OF PT. BANK RAKYAT INDONESIA (PERSERO) TBK - DELLAVITRYA PUTRI KHAIRUNNISA; Nola Halwatunnissa; Dian Hakip Nurdiansyah (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
This study uses PT Bank Rakyat Indonesia (Persero) Tbk as the object of research. This study wasconducted with the aim of analyzing how to forecast operating expenses at Bank BRI. The data used inthis study is secondary data, namely the operating expenses of PT Bank BRI obtained from theFinancial Statements of PT Bank BRI where the data is obtained from the official website of PT BankBRI from 2016 in the 1st quarter to 2020 in the 4th quarter. The method used in this study is the TimesSeries method by calculating the calculation of the error rate (the difference between the results of theincident and the results of the study). The type of times series method in this journal is the LeastSquare Method which is based on the calculations of previous years that have been running, while theMean Absolute Defiation (MAD) and Mean Absolute Percentage Error (MAPE) are used to calculatethe forecast error. The results of the study can be concluded that by using the least squares method topredict the operating expenses of PT Bank Rakyat Indonesia (Persero) Tbk in the 4th quarter of 2021and 2022 are Rp 96,140,848 and Rp 106,155,635, with forecasting errors obtained from calculations,namely MAD Rp 23,190,171 and MAPE 52 ,38%.